Constitutional Policy in Multilevel Government. The Art of Keeping the Balance. (December 2016) - Benz, Arthur
Abstract : Benz, Arthur (in cooperation with Andrea Fischer‐Hotzel, Dominic Heinz, Eike‐Christian Hornig, Jörg Kemmerzell, Bettina Petersohn). 2016. Constitutional Policy in Multilevel Government. The Art of Keeping the Balance. Oxford: Oxford University Press. ISBN: 9780198786078.http://ukcatalogue.oup.com/product/9780198786078.do